2005
DOI: 10.1002/humu.20250
|View full text |Cite
|
Sign up to set email alerts
|

Thymopoietin (lamina-associated polypeptide 2) gene mutation associated with dilated cardiomyopathy

Abstract: Thymopoietin or TMPO (indicated by its alternative gene symbol, LAP2, in this work) has been proposed as a candidate disease gene for dilated cardiomyopathy (DCM), since a LAP2 product associates with nucleoplasmic lamins A/C, which are encoded by the DCM gene LMNA. We developed a study to screen for genetic mutations in LAP2 in a large collection of DCM patients and families. A total of 113 subjects from 88 families (56 with familial DCM (FDC) and 32 with sporadic DCM) were screened for LAP2 mutations using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(113 citation statements)
references
References 43 publications
4
106
1
2
Order By: Relevance
“…LAP2α is linked to a laminopathy-type dilated cardiomyopathy, and loss of LAP2α-lamin A binding was observed for the mutated protein in vitro [114]. This finding again argues that disease-causing mutations in lamin A and LAP2α impair the functions of the nucleoplasmic complex.…”
Section: Impairment Of Lap Functions Gives Rise To Human Diseasesmentioning
confidence: 88%
“…LAP2α is linked to a laminopathy-type dilated cardiomyopathy, and loss of LAP2α-lamin A binding was observed for the mutated protein in vitro [114]. This finding again argues that disease-causing mutations in lamin A and LAP2α impair the functions of the nucleoplasmic complex.…”
Section: Impairment Of Lap Functions Gives Rise To Human Diseasesmentioning
confidence: 88%
“…For GFP-LAP2␣ carrying the DCM mutation, vector gAG43 was constructed by shuttling wild-type LAP2␣ cDNAs from gAG41 (18) into GFP destination vector pcDNA-DEST53 by the LR reaction (Invitrogen). The bacterial expression vectors encoding His-tagged LAP2␣ fragments are described elsewhere (16).…”
Section: Methodsmentioning
confidence: 99%
“…The Self-association of LAP2␣ Is Not Affected by a Diseaselinked Mutation-A mutation in the extreme C terminus of LAP2␣ has been linked to dilated cardiomyopathy in humans (18). The molecular mechanism of this disease is currently unknown, but we have shown that the disease-linked mutation in LAP2␣ decreased its binding affinity for lamins A and C. Therefore, we wondered whether the mutation could also interfere with the self-association of LAP2␣ molecules and whether this could contribute to the cellular defect in patient cells.…”
Section: Lap2␣ Forms Stable Complexes Of Defined Molecularmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, diseases affecting striated muscle comprise about 60% of the laminopathies. Of note, only ~50% of patients diagnosed with AD-EDMD or EDMD have EMD or LMNA mutations, indicating that mutations in other genes, perhaps those encoding proteins that interact with the lamins (e.g., LAP2), may account for the remaining 50% of patients [17,18].…”
Section: The A-type Laminopathiesmentioning
confidence: 99%